Inuit language in southern Labrador from 1694-1785 / La langue inuit au Sud du Labrador de 1964 à 1785 - Dorais, Louis-Jacques, 1945- (Book collections on Project MUSE., 1980)
Word and affix-lists, as well as grammatical observations, collected from texts written during 1694-1785.